احتساب الضريبة من الزكاة: Deducting Tax from Zakat - Mohd Noor, Azman; Fatime Eldersevi (International Journal of Al-Turath In Islamic Wealth and Finance, 2024)
الملخص الزكاة والضريبة نوعان من الالتزامات المالية التي تتفق مع بعضها في بعض الأمور ولكنها في الوقت نفسه تختلف عن بعضها في عدة أمور جوهرية، فلكل منهما غرضه وطبيعته الخاصة. فالزكاة اسم لقدر من المال يخرجه المسلم في وقت مخصوص لطائفة مخصوصة بالنية، وأما الضريبة فهي الفريضة المالية -النقدية- التي تأخذها الدول جبراً وبصفة نهائية من الأشخاص سواء أكانوا طبيعيين أم معنويين ودون مقابل مباشر لتحقيق منفعة عامة مع مراعاة المقدرة التكليفية للمكلف. واقتصرت الدراسات -حسب علم الباحثين- عن حكم احتساب الضريبة من الزكاة في البلدان الإسلامية، دون البلدان غير الإسلامية، فكان لابدّ من النظر في حكم احتساب الضريبة من الزكاة في البلدان غير الإسلامية، من خلال المنهج الاستقرائي التحليلي، وقد توصل البحث إلى أنه لا يجوز احتساب الضريبة من الزكاة إلا إذا كان وعاء الزكاة منفصلًا عن باقي أموال الضريبة إضافة إلى شروط أخرى كالتحقق من نية الدفع، ووجهة صرف الأموال، ومدى استفادة الفئات التي تستحق الزكاة منها. الكلمات المفتاحية: احتساب، زكاة، ضريبة، بلدان إسلامية، بلدان غير إسلامية. Abstract Zakat and tax are two types of financial obligations that share some similarities. Meanwhile, they differ in several other essential matters. Each has its own purpose and nature. Zakat is a specific amount of money that a Muslim gives at a specific time to a particular group with the intention of fulfilling a religious obligation. Tax, however, is a mandatory financial contribution – monetary in nature - that governments impose compulsorily on individuals, whether natural or legal persons, to achieve a public benefit, however, without direct compensation and considering the taxpayer’s ability to pay. To the researchers’ knowledge, all previous studies that examined the issue of calculating tax from zakat money have focused solely on the case in Islamic countries, excluding non-Islamic countries. Therefore, it was essential to investigate the issue in non-Islamic countries. The study adopted the analytical and inductive approaches. The study concluded that it is not permissible to calculate tax from zakat money unless the zakat money is kept separate from other tax funds, in addition to other conditions such as verifying the intention of payment, to whom the money will be given, and the extent to which the categories deserving of zakat benefit from it. Keywords: Deducting, Zakat, tax, Islamic countries, non-Islamic countries